Effectiveness of digital cognitive-behavioral therapy for insomnia alone or combined with sleep medication: A real-world evidence study - Julia Ribeiro da Silva Vallim; Gabriel Natan Pires; Renata Redondo Bonaldi; Marcio Andrei Zanini; Leticia Santoro Azevedo Soster; Silvério Garbuio; Ksdy Maiara Moura Sousa (Sleep Epidemiology, 2023)
Insomnia is a highly prevalent sleep disorder, but its first line of treatment (Cognitive Behavioral Therapy for Insomnia - CBTi) is not widely available and affordable. Digital therapy has been an alternative to these limitations and its combination with pharmacological treatment may improve patients' clinical outcomes and therapy adherence. This was a real-world evidence study aimed to evaluate the efficacy of a CBTi smartphone app combined or not with sleep medication, based on a sample of users of a CBTi smartphone app (SleepUp®) registered between June 2020 and June 2022. Individuals were categorized into two groups (“dCBTi alone” and “dCBTi combined”) according to their self-reported use of sleep medication on the first day of treatment. Assessments were made based on the self-report of sleep logs (sleep quality and efficiency) and on insomnia severity (Insomnia Severity Index). Comparisons were made considering the first entry (baseline) and the mean of the last three days in which sleep logs were filled out (final). The final samples comprised 143 individuals: 73 (51%) reported using sleep medication at baseline, while 70 (49%) did not. In both groups, there was an improvement in sleep quality, (p<0.001), sleep efficiency (p<0.001), and insomnia severity (p<0.001). The magnitude of effects on sleep efficiency and insomnia severity was greater in the dCTBi combined group. This result indicates that dCBTi can be useful as an adjuvant treatment for insomnia.